Effects of recreational diving and snorkeling on the distribution and abundance of surgeonfishes in the Egyptian Red Sea northern islands - Walaa Shaban; Salah E. Abdel-Gaid; Hussein A. El-Naggar; Mansour A. Bashar; Mostafa F. Masood; El-Sayed S. Salem; Ahmed N. Alabssawy (Egyptian Journal of Aquatic Research, 2020)
This work aimed to study the effects of recreational diving and snorkeling on the distribution, diversity, and abundance of surgeonfishes in six northern islands, different in their diving and snorkeling load, at the Hurghada area in the Egyptian Red Sea waters. SCUBA diving survey was conducted in summer 2019 using transect technique in the reef flat and reef slope in the study sites to compare total and single surgeonfish species census among sites and microhabitats. A total of six species of surgeonfish belonging to three genera were recorded during the current survey, including Zebrasoma xanthurum, Zebrasoma desjardinii, Acanthurus gahhm, Acanthurus sohal, Naso lituratus, and Naso unicornis. Z. desjardinii was the most abundant species, recording 41.2% relative abundance, followed by Acanthurus sohal (19%). In all sites, surgeonfish species diversity and average/total abundance in reef flat was always higher than that recorded in the reef slope. Meanwhile, the recreational effect results showed that, in reef flat habitats, surgeonfishes total/average abundance was inversely related to the numbers of divers and snorkelers across survey sites. In contrast, deeper habitat at the opened reef edge exhibited inverse distribution pattern, whereas, the obtained results showed that surgeonfish preferred the reef edge when the diving activities load increased.